Incidence and Predictors of Tuberculosis among HIV Positive Children at University of Gondar Referral Hospital, Northwest Ethiopia: A Retrospective Follow-Up Study - Ayalaw, Sualiha Gebeyaw (Int Sch Res Notices, 2015)
Background. The aim of this study was to determine the incidence of tuberculosis and its predictors among HIV positive children. Methods. A six-year retrospective follow-up study was conducted among HIV infected children aged less than 15 years. Life table was used to estimate the cumulative probability of tuberculosis free survival. Cox proportional hazards model was used to identify predictors of tuberculosis. Results. A total of 271 HIV positive children were followed for six years and produced 1100.50 person-years of observation. During the follow-up period 52 new TB cases occurred. The overall incidence density of TB was 4.9 per 100 PY. Inappropriate vaccination [AHR: 8.03 (95% CI; 4.61–13.97)], ambulatory functional status [AHR: 1.99 (95% CI; 1.04–3.81)], and having baseline anemia [AHR: 2.23 (95% CI; 1.19–4.15)] were important predictors of time to TB occurrence. Conclusion. TB incidence rate was high. Early diagnosis and treatment of anemia and strengthening immunization program would reduce the risk of TB occurrence.